IMPACT OF CIRCULAR ECONOMY PRACTICES ON EXPORT PERFORMANCE - Khayat, Sahar Hassan (International Journal of Research -GRANTHAALAYAH, 2026)
This study aims to explore the impact of circular economy practices on export performance and environmental performance within the framework of a developing economy such as Jordan. Moreover, the mediating role of environmental performance on the nexus between circular economy practices and export performance. This study used a cross-sectional survey questionnaire from 279 managers of manufacturing firms in Jordan. To ensure diversity in the sample, this study included firms from different industry types. The structural equation modeling approach was performed with reliability and validity analysis to test the study hypothesis. The findings showed that circular economy practices significantly and positively influence environmental and export performance. Environmental performance also significantly and positively affects export performance. Moreover, it is also observed that environmental performance mediates the association between export performance and circular economy practices. This finding are intended to encourage the adoption of circular economy practices across the manufacturing firms of Jordan to reap economic gains by stimulating their exports through enhancement in environmental performance.